Midwife-led care in newborns with Edwards syndrome - Julia M. Donarska; Joanna Moćkun-Pietrzak; Hanna Popowicz (Termedia Publishing House, 2024)
Edwards syndrome is a chromosomal disorder that involves the presence of 3 copies of chromosome 18. The extra genetic material results in several characteristic phenotypic features, such as polydactyly, agenesis of the corpus callosum, and heart defects. A pre-disposing factor for Edwards syndrome is the mother's age. Women are choosing to become pregnant later in life, and thus the number of children with Edwards syndrome is increasing. This problem motivated the present study, the purpose of which was to present the problems and difficulties associated with the care of a newborn with Edwards syndrome and to discuss the management of patient and family care. The study used a qualitative case study method. During the creation of the nursing process, the ICNP method was used. Written consent from the child's mother and approval from the Bioethics Committee at the Medical University of Gdansk (KB/8/2024) were obtained before the study was conducted.